Pioneers in microbiology the human side of science - Chung, King-Thom; Liu, Jong-Kang (World Scientific, 2018)
"Pasteurization, penicillin, Koch's postulates, and gene coding. These discoveries and inventions are vital yet commonplace in modern life, but were radical when first introduced to the public and academia. In this book, the life and times of leading pioneers in microbiology are discussed in vivid detail, focusing on the background of each discovery and the process in which they were developed - sometimes by accident or sheer providence."--Publisher description.